Sebuah Studi Pasangan Kedekatan di Late Late Show With James Corden: Sebuah Studi Kasus di Sore dengan Pangeran Harry dan James Corden Episode - Mutiara Indah; Nisa Nur Farida (Neolectura, 2022)
This research entitled A Study of Adjacency Pairs in The Late Late Show with James Corden, A Case Study in An Afternoon with Prince Harry and James Corden Episode investigates particular social action which is indicated from pair utterances and preference. This research tries to find kind of adjacency pairs which are included in conversation between James and Prince Harry, which are the dominant types of adjacency pairs, and the particular social action that is revealed between James and Prince Harry. The data were analyzed using Harvey Sack (1986) and Yule (1996) theory. This research applied descriptive qualitative method with case study design to obtain the result. the data that were analyzed were taken from The Late Late Show with James Corden YouTube channel that were including transcribing, identifying, coding, describing and interpreting. The researcher found thirty-five pairs utterances that construct in the conversation between James Corden and Prince Harry which are ten types of adjacency pairs found. At last, researcher found that question-answer is the dominant types of adjacency pairs that relate with this research subject, Talk Show, which absolutely will contain question answer segment and preferred response is the dominant preference structure which indicates both James and Prince Harry close to each other in pragmatic perspective.